Pendampingan Mahasiswa Prodi Bimbingan Konseling Kristen dalam Pelaksanaan Magang Mikro Konseling di UPT SDN 13 Gandangbatu Sillanan, Tana Toraja, Sulawesi Selatan - Setblon Tembang; Ekkleysia Putri Saleppa (Jurnal Informasi Pengabdian Masyarakat, 2024)
An internship is an integration between theory and practice in the field. Carrying out an internship is an opportunity for students to apply and develop the theory they have obtained in learning with direct practice in the field. Micro Counseling is intended to equip Christian Counseling Guidance Study Program students as prospective counseling guidance teachers. In implementing this micro counseling internship activity, assistance from the supervisory lecturer is needed to make this activity run smoothly. In the implementation of assisting students of the Christian Counseling Guidance Study Program in carrying out micro counseling, it is divided into three stages, namely the preparation stage, the implementation stage, and the final stage. The results of micro-counseling internship assistance at UPT SDN 13 Gandangbatu Sillanan, show that students can assess the need for guidance and counseling services in elementary schools, develop Christian Counseling Guidance Study program services for elementary school students, and are directly involved in implementing counseling guidance services in schools so that students have sufficient experience and skills to become professional counseling guidance teachers and be able to carry out counseling guidance services in the future responsibly and professionally